EFISIENSI ILUSI FISKAL DAN PENGARUH PENGELUARAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI (Kasus : Kabupaten di Provinsi Jawa Timur Tahun 2016 s.d. 2018) - Farah Aisha Nur Afifah (LPPM University 17 Agustus 1945 Samarinda, 2021)
The research is to prove that there was a fiscal illusion in district government spending in East Java in 2016-2018, and to prove that the fiscal illusion that occurred in government spending had an influence on the economic growth of each district. In fiscal decentralization in the era of regional autonomy, there is a phenomenon that each regional government still depends on financing activities from government transfer funds rather than receiving local revenue to finance regional expenditures. Even though government spending has increased every year, it is not in balance with economic growth. In this study it can be proven that there is a fiscal illusion in district government spending in East Java 2016-2018, this fiscal illusion affects the economic growth of each region. To increase economic growth and reduce regional unemployment rates, it is necessary to make efforts to increase capacity and fiscal independence as well as increase the labor force participation rate.Keywords: fiscal illusion, government spending, local government, economic growth, East Java.